2022
DOI: 10.3389/fnut.2022.804210
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Killed Lacticaseibacillus paracasei GMNL-653 Exerts Antiosteoporotic Effects by Restoring the Gut Microbiota Dysbiosis in Ovariectomized Mice

Abstract: Osteoporosis is a metabolic inflammatory disease, an imbalance occurs between bone resorption and formation, leading to bone loss. Anti-inflammatory diet is considered having the potential to ameliorate osteoporosis. Heat-killed probiotics exhibit health benefits in relation to their immunomodulatory effects, but the detail mechanism involved in gut microbiota balance, host metabolism, immunity, and bone homeostasis remains unclear. In this study, we evaluated the antiosteoporotic effects of heat-killed Lactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…In this study, 16S ribosomal RNA gene amplicon sequencing was performed as previously described [ 32 ]. Ileum samples were collected from each group after 12 days, and all specimens were extracted using a Qiagen DNA kit (Qiagen, Hilden, Germany) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, 16S ribosomal RNA gene amplicon sequencing was performed as previously described [ 32 ]. Ileum samples were collected from each group after 12 days, and all specimens were extracted using a Qiagen DNA kit (Qiagen, Hilden, Germany) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The processing and statistical analysis of meta-taxonomic data were performed as previously described [ 32 ]. To determine the difference in microbial composition among groups, the Shannon diversity index was used to analyze the alpha diversity of taxonomic composition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding differences related to BMI and medications, the study suggested an adverse effect of Lactobacillus on osteoporosis (Das et al, 2019). In contrast, part of Lactobacillus belonging to this genera, such as Lactobacillus acidophilus, Lacticaseibacillus paracasei GMNL-653, and Lactobacillus reuteri et al, were thought to positively regulate bone health (Dar et al, 2018;Lee et al, 2021;Jhong et al, 2022). Britton et al showed that Lactobacillus reuteri suppressed ovariectomyinduced increases in bone marrow CD4+ T lymphocytes and inhibited estrogen deficiency-induced bone resorption and bone loss (Britton et al, 2014).A study using a mouse model with gut microbial dysbiosis after antibiotic treatment found that Lactobacillus reuteri prevented osteoblastopenia and increased osteoclast activity, thereby preventing trabecular bone loss in the femur and spine and exerting a positive skeletal effect.…”
Section: Firmicutesmentioning
confidence: 99%
“…After excluding differences related to BMI and medications, the study suggested an adverse effect of Lactobacillus on osteoporosis ( Das et al., 2019 ). In contrast, part of Lactobacillus belonging to this genera, such as Lactobacillus acidophilus, Lacticaseibacillus paracasei GMNL-653, and Lactobacillus reuteri et al, were thought to positively regulate bone health ( Dar et al., 2018 ; Lee et al., 2021 ; Jhong et al., 2022 ). Britton et al.…”
Section: Intestinal Microbiota Classification Characteristics and Bon...mentioning
confidence: 99%